The Dynamics of Human and Water Relations: Analysis of the CSR Program Kampung Kreatif Karisma Pertamina (K3P) in the Serayu River Watershed - Arifin, Muhson; Trianingrum, Suci; Dewi, Primatika Pramana; Perkasa, Agil Bagus Putra (Global Writing Academica Researching and Publishing, 2024)
For some environmentalists, issues such as erosion, flooding, and landslides caused by an abundance of water are considered purely environmental problems. However, multiple case studies conducted in Karangrena Village, specifically in the Serayu Watershed, reveal a different perspective. By examining two interrelated programs the Biodiversity Protection and Reforestation Program of the Serayu Watershed, which has been implemented since 2013, followed by the CSR Program “Kampung Kreatif Karisma Pertamina” (K3P) that began in 2020 and continues to this day valuable reflections and findings have emerged. First, the issue of water as an environmental entity cannot be separated from social, economic, and even cultural aspects of life. Second, an abundance of water does not automatically equate to easy access to water. Third, solutions to water-related problems cannot be resolved through purely environmental efforts. Fourth, among communities living in the Serayu Watershed, perceptions of water are not singular; on one hand, water can be a threat as it is a source of disasters such as erosion, flooding, and landslides. On the other hand, water is a valuable resource, although the abundance of water can sometimes be difficult for them to access. Thus, the two programs facilitated by PT Pertamina Patra Niaga Fuel Terminal Maos, in collaboration with community groups in Karangrena Village, have gradually been able to address social, economic, environmental, and cultural issues in the Serayu Watershed.